Diet Composition and Feeding Strategies of the Stone Marten (Martes foina) in a Typical Mediterranean Ecosystem - Dimitrios E. Bakaloudis; Christos G. Vlachos; Malamati A. Papakosta; Vasileios A. Bontzorlos; Evangelos N. Chatzinikos (The Scientific World Journal)
Stone martens (Martes foina) are documented as generalist throughout their distributional range whose diet composition is affected by food availability. We tested if this occurs and what feeding strategies it follows in a typical Mediterranean ecosystem in Central Greece by analysing contents from 106 stomachs, seasonally collected from three different habitats during 2003–2006. Seasonal variation in diet and feeding strategies was evident and linked to seasonal nutritional requirements, but possibly imposed by strong interference competition and intraguild predation. Fleshy fruits and arthropods predominated in the diet, but also mammals and birds were frequently consumed. An overall low dietary niche breadth (BA=0.128) indicated a fruit specialization tendency. A generalised diet occurred in spring with high individual specialisation, whereas more animal-type prey was consumed than fruits. A population specialization towards fruits was indicated during summer and autumn, whereas insects were consumed occasionally by males. In those seasons it switched to more clumped food types such as fruits and insects. In winter it selectively exploited both adult and larvae insects and partially fruits overwinter on plants. The tendency to consume particular prey items seasonally reflected both the population specialist behaviour and the individual flexibility preyed on different food resources.